FRACTAL MODELING OF OIL AND GAS PRODUCTION PROCESSES: NON-LINEARITY, NON-UNIFORMITY, UNCERTAINTY - Abdurakhmanov Abdulaziz Abdug’ani o’g’li; Anarova Shaxzoda Amanbayevna (Galaxy International Interdisciplinary Research Journal, 2022)
Fractal representations simplify the analysis of the turbulent movement of a liquid or gas, as well as the flow process, which is important for the technology of field development. At the same time, in geological processes, nanoscale components and phenomena act as the main ones where the difference in the properties of three-dimensional and two-dimensional (surface) states of matter is important. Fundamentally new methods of complex analysis of oil and gas systems, currently being developed on the basis of modern achievements in fractal physics of nanotechnology, geophysics and mathematical physics, make it possible to concretize information about their dynamics, taking into account the complexity of the topology of oil and gas reservoirs, the porous structure of stressed oil and gas layers, changes in the state of deposits under the influence of technogenic processes. Fractal and nanostructural modeling helps to determine the current level of self-organization and manage balanced field development, and, ultimately, significantly increase the final coefficient of oil and gas extraction.